Smart home technologies that support independent living: challenges and opportunities for the building industry – a systematic mapping study. (2nd January 2017) - Labonnote, Nathalie; Høyland, Karin
ABSTRACT: Objective: To provide an overview of the state of research concerning smart technologies that support independent living in buildings, as well as a deeper literature review of the specific challenges for the building industry. Methods : A systematic mapping methodology was applied in this study to provide basis knowledge on the state of the art. The initial search on three databases gave 3485 articles. Of these, 610 articles were finally selected as relevant to the study after removing the duplicates and screening by applying inclusion and exclusion criteria based on titles and abstracts. Keywording was performed in order to answer the research questions of the study. Results : Results from the systematic mapping technology allow the detection of almost mature technologies, as well as promising technologies and research gaps. Results from the deeper literature review have identified challenges and new trends specific to the building industry. Conclusions : Efforts are still needed for the building industry in order to contribute significantly to meeting societal needs. Further research : Research fields that would benefit from further research are highlighted.